Aditivos na terminação intensiva de bovinos de corte a pasto - Anjos, Elismar dos (2019)
The objective of this work was to evaluate the productive performance and behavior of beef cattle in intensive pasture system, receiving high doses of supplement containing non - antibiotic additives in replacement of virginiamycin in the dry season in the North of the State of Mato Grosso. The experiment was structured according to a completely randomized design (DIC), with four treatments with ten replications. The supplements were formulated to be iso-nitrogenous, containing 15% crude protein (% DM), offered ad libitum daily at 8 o'clock in the morning. According to the differentiation of the used additives, the treatments were described as: VM - supplement containing non-ionophore additive (virginiamycin); ADV - supplement containing yeast-based probiotic (3g.100kg BW-1 ) to replace virginiamycin; TN1,4 - supplement containing 1.4g.kgDM-1 of tannin to replace virginiamycin; TN2.1 - supplement containing 2.1 g.kgDM-1 of tannin to replace virginiamycin. The experiment was carried out in the experimental area belonging to Embrapa Agrossilvipastoril, in the city of Sinop - MT. Forty Nellore, non-castrated cattle with mean age of 24 ± 2 months and initial mean body weight of 415 ± 5 kg were used. The total area had 7.5 ha divided with electric fences in 4 pickets with 1.88 ha each, formed with Urochloa brizantha cv. BRS Piatã, deferred in February 2017. The total forage mass, measured in kg.MS.ha-1, was collected every 14 days. The animals were weighed, with fasting of food and water of 16 hours in the first and last weighing, for later determination of the average weight gain daily and without fasting every 28 days. The animals fed supplements TN1,4 and TN2,1 showed higher dry matter intake of the supplement in% of live weight, higher average daily gains and mean carcass gain (kg / animal / day), higher final live weight, weight of final carcass, carcass weight, and carcass gain at. No significant difference was observed for carcass yield, feed efficiency, biological efficiency and weight gain (%) yield for animals fed supplements containing different additives. Despite the high doses of concentrate in the diet, the treatments did not promote changes in the metabolic profile of the animals. No evidence of pathological problems was observed, such as liver lesions and / or failure, renal and intestinal disorders. All treatments presented positive economic viability, but the ADV treatment containing yeasts as an additive presented higher profitability for the activity, approximately R $ 1,027.28 per hectare (R$ / ha). The use of 1.4 g.kg DM-1 of condensed tannin (TN1.4) and yeast (ADV) added to concentrate xiii feed in the form of an additive at the intensive termination of Nellore beef cattle on pasture yielded better performance results be used as an additive to replace growth promoters with antibiotic characteristics. The animals reduced the time of water intake and leisure time while increasing the grazing time and the time during rumination during the rainy season. The non-antibiotic additives maintained the same feed intake time, besides not interfering with the period. The concentrated supplement can be supplied only once a day to the animals, since they voluntarily control the consumption. The animals reduced the time of water intake and leisure time while increasing the grazing time and the time during rumination during the rainy season. The treatments TN1,4 and TN2,1 maintained the same time of feed intake, besides it does not suffer interference of the period, being able to be supplied only once a day to the animals, since they control voluntarily the consumption.